(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aimed to determine the availability of the dimensions of the strategic orientation: entrepreneurial orientation, market orientation, technology orientation in the branches of private commercial banks in the Syrian coast. And discuss their hypotheses While in relation to the research methods, a questionnaire was developed through the researcher’s view of the published literature as a tool for collecting the primary data, and the grades were distributed to the items of the questionnaire according to the Likert pentagon scale, and the research sample was represented by 110 individual staff from banks, and then he conducted a field study for the purpose of demonstrating this Relationship. The study concluded that bank management does not accept or implement ideas that were not previously thought about, and banks do not have a willingness to take risks as a result of providing new services, and that banks do not seek customer opinions to know their satisfaction with the services provided, and the average responses of the sample members to a variable Orientation towards competitors 2.984, which indicates a lack of availability after the orientation towards competitors as one of the dimensions of the strategic direction in the banking sector.